Cholesterol sulfate fluidizes the sterol fraction of the stratum corneum lipid phase and increases its permeability - Fandrei, Ferdinand; Engberg, Oskar; Opálka, Lukáš; Jančálková, Pavla; Pullmannová, Petra; Steinhart, Miloš; Kováčik, Andrej; Vávrová, Kateřina; Huster, Daniel (Journal of lipid research, 2022)
Desulfation of cholesterol sulfate (CholS) to cholesterol (Chol) is an important event in epidermal homeostasis and necessary for stratum corneum (SC) barrier function. The CholS/Chol ratio decreases during SC maturation but remains high in pathological conditions, such as X-linked ichthyosis, characterized by dry and scaly skin. The aim of this study was to characterize the influence of the CholS/Chol molar ratio on the structure, dynamics, and permeability of SC lipid model mixtures. We synthesized deuterated CholS and investigated lipid models with specifically deuterated components using 2H solid-state NMR spectroscopy at temperatures from 25°C to 80°C. Although the rigid acyl chains in ceramides and fatty acids remained essentially rigid upon variation of the CholS/Chol ratio, both sterols were increasingly fluidized in lipid models containing higher CholS concentrations. We also show the X-ray repeat distance of the lipid lamellar phase (105 Å) and the orthorhombic chain packing of the ceramide's acyl chains and long free fatty acids did not change upon the variation of the CholS content. However, the Chol phase separation visible in models with high Chol concentration disappeared at the 50:50 CholS/Chol ratio. This increased fluidity resulted in higher permeabilities to model markers of these SC models. These results reveal that a high CholS/Chol ratio fluidizes the sterol fraction and increases the permeability of the SC lipid phase while maintaining the lamellar lipid arrangement with an asymmetric sterol distribution.
Keywords: sterols; Cholesterol; cholesterol; permeabilita; Permeability; kůže; ceramides; Ceramides; Epidermis; permeability; lipids; skin; steroly; estery cholesterolu; ceramidy; order parameter; lipid packing; Cholesterol Esters; Sterols; epidermis; nanostructure; Skin